Nexus Between In-Store Design Cues and Impulse Purchasing Behavior at Supermarkets in Yaoundé, Cameroon: Do Gender and Age Matter? - Sigimi, Fidelis Vernyuy; Jumbo, Urie Eleazar; Chiatii, Elizabeth Ankiambom (Business Perspective Review, 2024)
Purpose: This study seeks to assess the relationship between in-store design cues (store layout, product placement, signage, and point of sales display) and impulse purchase behavior at supermarkets in Yaoundé, Cameroon. It also explores the moderating effects of age and gender on this relationship. Methods: The study adopted a quantitative design with the help of a model with four exogenous variables, two moderating variables, and one endogenous variable adapted from the stimulus organism response (S-O-R) model of Zajonc (1980). The questionnaires were administered both physically and online to 429 shoppers from four selected supermarkets. The multiple correspondence analysis was used to construct indexes for store layout, product placement, signage, and point of sales display. The ordinary least square estimation technique was used to test the hypotheses of the study. The moderating effects of gender and age were done by interacting the two moderating variables with the components of in-store design cues. Results: Results revealed that layout quality and point of sales display exerted significantly positive effects on shoppers’ impulse purchasing behavior while signage and product placement had a positive but insignificant effect on customers’ impulse purchasing behavior. The results also revealed a negative but insignificant moderating effect of gender while the moderating effect of age was positive and significant. An overall significant effect of design cues implies that the in-store design cues were found to be attractive and stimulating by the customers. Implications: The study therefore concluded that an improvement in the store design features will act as a significant stimulus for customers’ increased impulse purchases. This study has significant practical and theoretical implications in the area of consumer behavior in the context of developing countries, like Cameroon.